Dynamics Modeling and Simulation of Dual-arm Robot based on the Improved Udwadia-Kalaba Equation - Jia Liu; Yuanping Shi; Hongqiang Sun; Rong Liu (Jixie chuandong)
A new idea for dynamics modeling of multibody systems is provided by the Udwadia-Kalaba equation. The generalized constrained relationship is established to obtain the constraint relations in analytical form. The improved Udwadia-Kalaba equation is proposed to eliminate the error which generates during the modeling process by Udwadia-Kalaba equation. The stimulation results show that the proposed methods can be more effectively utilized in dynamics modeling of dual-arm robot.